Islamic Fundamentalism as A Signifier of The Sixth Phase of Globalization - Mohammad Hasan Basri (Al-Ulum, 2011)
This article examines Islamic fundamentalism through a historical perspective on globalization offered by Roland Robertson, the theory of Islamic fundamentalism and its relation to the involvement of youth in Indonesia. In theory, Islamic fundamentalism is divided into two classifications. First is the "continuity and change", the development of fundamentalism in Islam is both continuity and change in Islamic history. The second theory is the "challenges and opportunities". The basic assumption of this theory is that the crisis in the modern Muslim world, accumulation social, political, and cultural are consider the main factors influence Islamic fundamentalism. Advanced technology in communications, information, and the country's transportation networks around the world; variety of shows, events, and the phenomenon will spread rapidly from one country to another.